Quantification of Visual Fixation Behavior and Spatial Orientation Memory in Drosophila melanogaster - Yen, Hung-Hsiu; Han, Rui; Lo, Chung-Chuan (Frontiers in Behavioral Neuroscience, 2019)
Drosophila Melanogaster has been shown to exhibit short-term orientation memory by fixating on orientations toward previously displayed visual landmarks. However, the fixation behavior varies and is often mixed with other types of movement. Therefore, carefully designed statistical measures are required in order to properly describe the characteristics of the fixation behavior and to quantify the orientation memory exhibited by the fruit flies. To this end, we propose a set of analytical methods. First, we defined the deviation angle which is used to quantify the deviation of the fruit fly’s heading from the landmark positions. The deviation angle is defined based on the fruit fly’s perspective and is able to reveal more task-relevant movement patterns than the commonly used definition which is based on the “observer’s perspective.” We further introduce a temporal deviation angle plot which visually presents the complex movement pattern as a function of time. Next, we define the fixation index which tolerates fluctuation in the movement and performs better in quantifying the level of fixation behavior, or the orientation memory, than the conventional method.